Distinguishing transcreation from translation: exploring strategies to render gender stereotypes - Zhu, Li; Ang, Lay Hoon; Sun, Yanna (SAGE Publications, 2024)
Academics have long debated the similarities and differences between translation and transcreation. Despite extensive discussion, few studies have examined these distinctions through the lens of the strategies adopted. In response, this study explores how strategies of translation and transcreation are utilized to render gender stereotypes within a specific text type. The theoretical framework is grounded in Karoubi’s categorization of translating gender and Ketola’s types of transcreation strategies, which focus on how gender is interpreted and represented across languages and cultures. Utilizing a qualitative approach, this research analyzes English fragrance product descriptions and their Chinese versions across 12 brands, comprising 224 pairs of descriptions. The findings reveal significant differences in the use of target culture-oriented strategies, with transcreation employing these strategies in approximately 90% of cases, compared to only about 50% in translation. The results suggest that the primary distinction between translation and transcreation lies in the extent to which practitioners alter the source text when creating new content. Moreover, identifying strategies of translation and transcreation based on the established framework could also help distinguish transcreation from translation. These findings contribute new empirical insights to the ongoing debates about the distinctions between translation and transcreation.